1996
DOI: 10.1177/154596839601000306
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator Dependency in ALS: Management, Disease Progression, and Issues of Coping

Abstract: The natural progression of amyotrophic lateral sclerosis (ALS) leads to respiratory failure and death. Artificial ventilation can prolong the course, leading to extreme degrees of weakness and dependence. Little specific information is available to counsel ALS patients about making the decision for artificial ventilation. In order to gain more information, we visited four ventilator-dependent ALS patients and their primary caregivers. We determined the neurologic state and level of function of the patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…For example, despite compromised physical function, the majority of people with ALS rated their QOL as 8 or better on a scale of 1 to 10 [3,4]. Several studies have found that even when people with ALS are supported by mechanical ventilation, they are generally satisfied with their quality of life, are not depressed, and have a positive worldview (e.g., [5,6]). …”
Section: Introductionmentioning
confidence: 99%
“…For example, despite compromised physical function, the majority of people with ALS rated their QOL as 8 or better on a scale of 1 to 10 [3,4]. Several studies have found that even when people with ALS are supported by mechanical ventilation, they are generally satisfied with their quality of life, are not depressed, and have a positive worldview (e.g., [5,6]). …”
Section: Introductionmentioning
confidence: 99%
“…Assisted ventilation can either be noninvasive (masks or nasal cannula) or invasive (intubation), and it has been shown to improve life expectancy for individuals with DMD (Eagle et al, 2002) and MND (Bromberg, Forshew, Iaderosa, & McDonald, 1996). Hirano, Yamazaki, Shimizu, Togari, and Bryce (2006) found that economic, social, and cultural factors may influence the decision for individuals and families to elect to pursue assisted ventilation.…”
Section: Assisted Ventilationmentioning
confidence: 99%
“…However, assisted ventilation can cause a considerable amount of stress and burden for family members (Bromberg et al, 1996;Carnevale, Alexander, Davis, Rennick, & Troini, 2006;Gelinas, O'Connor, & Miller, 1998;Heaton, Noyes, Sloper, & Shah, 2005;Mah et al, 2008;Moss et al, 1996). In fact, some MND caregivers expressed anger and resentment over the assisted ventilation process (Gelinas et al, 1998).…”
Section: Assisted Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other target groups have been adult patients in health care 17 and child health clinic 18 and maternity clinic clients 19 . The only studies found in Medline, CINAHL and Sociofile on patients' decision‐making on home respiratory care 9,10 , 20,21 were qualitative.…”
Section: Who Participates?mentioning
confidence: 99%